Landscape of tumor and immune system cells-derived exosomes in lung cancer: mediators of antitumor immunity regulation - Castillo-Peña, Alejandro; Molina-Pinelo, Sonia (Frontiers in Immunology, 2023)
The immune system plays a critical role in cancer, including lung cancer, which is the leading cause of cancer-related deaths worldwide. Immunotherapy, particularly immune checkpoint blockade, has revolutionized the treatment of lung cancer, but a large subset of patients either do not respond or develop resistance. Exosomes, essential mediators of cell-to-cell communication, exert a profound influence on the tumor microenvironment and the interplay between cancer and the immune system. This review focuses on the role of tumor-derived exosomes and immune cells-derived exosomes in the crosstalk between these cell types, influencing the initiation and progression of lung cancer. Depending on their cell of origin and microenvironment, exosomes can contain immunosuppressive or immunostimulatory molecules that can either promote or inhibit tumor growth, thus playing a dual role in the disease. Furthermore, the use of exosomes in lung cancer immunotherapy is discussed. Their potential applications as cell-free vaccines and drug delivery systems make them an attractive option for lung cancer treatment. Additionally, exosomal proteins and RNAs emerge as promising biomarkers that could be employed for the prediction, diagnosis, prognosis and monitoring of the disease. In summary, this review assesses the relationship between exosomes, lung cancer, and the immune system, shedding light on their potential clinical applications and future perspectives.